A systematic review: perivascular epithelioid cell tumor of gastrointestinal tract. Issue 28 (July 2016) - Chen, Zehong; Han, Siqi; Wu, Jialin; Xiong, Minmin; Huang, Yanqiao; Chen, Jianhui; Yuan, Yujie; Peng, Jianjun; Song, Wu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Perivascular epithelioid cell tumor (PEComa) is a rare entity with distinctive morphology and of expressing myomelanocytic markers. Gastrointestinal tract (GI) is one of the most common anatomic sites of origin and counts for 20% to 25% of all reported cases of perivascular epithelioid cell tumors not otherwise specified (PEComas-NOS). However, the biologic behavior of perivascular epithelioid cell tumors of gastrointestinal tract (GI PEComas-NOS) is still unclear. The aim of conducting this systematic review is to sum up what is known so far of the epidemiology, natural history, management and prognosis of GI PEComas-NOS. A systematic research was performed on PubMed and EMBASE using the following terms: ("perivascular epithelioid cell tumor" or "PEComa") and ("gastrointestinal tract" or "GI" or "oral " or "mouth" or "esophagus" or "gullet" or "gastric" or "stomach" or "duodenum" or "jejunum" or "ileum" or "cecum" or "colon" or "colorectal" or "sigmoid" or "rectum" or "anus" or "mesentery") up to December 1, 2015. Retrieved GI PEComas-NOS publications, which included these terms, contains case reports, case series to case characteristic researches. A total of 168 articles were reviewed, 41 GI PEComa-NOS English studies among which were retrieved for analysis. We reviewed epidemiology, natural history, management and prognosis of GI PEComa-NOS. Generally GI PEComa-NOS is believed to have women predomination. The most frequently involved location is colon with non-specific clinical signs. Pathologically, GI PEComas-NOS shows epithelioid predominance (70%), meanwhile coexpresses melanocytic and muscle markers characteristically, while immunohistochemistry is a useful tool for identify, which indicates that HMB-45 is regarded as the most sensitive reagent. Complete resection served as mainstay of treatment, while chemotherapy should be unanimously considered to apply in malignant cases. Eventually, it is necessary for closed and long-term follow-up with endoscope and imaging for ruling out local recurrence or distant metastasis of this tumor. GI PEComas-NOS lives with unclear behavior. There are still many unverified clinicopathological issues of GI PEComas-NOS that needs to be clarified. Further studies and analyses concerning this rare entity should be brought out. Thus, the randomized clinical researches (RCTs) are required to be conducted.